National legal regulation of foreign investments - Shan, Li (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article analyzes the international and national practice of legal regulation of foreign investments. The main issues necessary to attract foreign investors are also indicated. Adoption of special laws on foreign investment is caused by the necessity to attract foreign investment into the country's economy by creating a favorable climate and granting preferential treatment for foreign investments. The author emphasizes that the creation of the appropriate system of legal regulation of activities with the participation of foreign investors is not limited by creating a favorable regime for foreign investments or granting them benefits and preferences, first of all, it should take aim at ensuring and protecting social (public) interests. Therefore, the state has the right to install certain restrictions in implementation of foreign investments. As it is proved by the international practice of attracting foreign investment, the introduction of restrictions and withdrawals from the national regime and most-favored-national treatment for the placement of foreign investment is possible even in the conditions of maximized full liberalization of foreign investors’ activity. Disclosing the general trend in the development of national legislation on foreign investments in different countries, the author believes that after the end of the investment policy aimed at attracting foreign investment that has led to economic growth and the welfare of the population, another process begins, when the differences between different legal regimes of foreign and national investment are obliterated. As a result, special legislation on foreign investment is replaced by a general legislation, including investment, civil, commercial legislations, etc.
Шетел инвестицияларын ұлттық-құқықтық реттеу
Национальное-правовое регулирование иностранных инвестиций
Keywords: investment; national investment; foreign investment; legislation on foreign investments; investment activity; foreign investor; investment policy; foreign capital; investment area; investment field; investing